Proceedings of the 51st Hawaii International Conference on System Sciences 2018
DOI: 10.24251/hicss.2018.244
|View full text |Cite
|
Sign up to set email alerts
|

Learning in the Wild: Coding Reddit for Learning and Practice

Abstract: This paper introduces a 'learning in the wild' coding schema, an approach developed to support learning analytics researchers interested in understanding the different types of discourse, exploratory talk, and conversational dialogue happening on social media. The research examines how learner-participants ('Redditors') are leveraging subreddit communities to facilitate selfdirected informal learning practices on the social networking site. The coding schema is tested and applied across four 'Ask' subreddit co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 30 publications
(20 reference statements)
0
8
0
3
Order By: Relevance
“…Through its rules and norms, r/AskHistorians extends existing models of public scholarship that focus on information dissemination, open access, and knowledge translation to an instructional model of information literacy that builds readers' skills, such as learning historical methods. The community also teaches readers how to identify and account for bias in source material [25], and the discussions in which users read and engage provide rich opportunities for learning in the wild [29,41].…”
Section: Inverting Design and Culture To Foster Trustmentioning
confidence: 99%
“…Through its rules and norms, r/AskHistorians extends existing models of public scholarship that focus on information dissemination, open access, and knowledge translation to an instructional model of information literacy that builds readers' skills, such as learning historical methods. The community also teaches readers how to identify and account for bias in source material [25], and the discussions in which users read and engage provide rich opportunities for learning in the wild [29,41].…”
Section: Inverting Design and Culture To Foster Trustmentioning
confidence: 99%
“…Studies form a social learning analytics perspective have built on [37] to explore online interaction as a step toward automated analysis. For example, one study developed codes for interaction in MOOCs with categories of challenge, evaluation, extension and reasoning [35]; Another [18,20] coded more generally for interaction and argumentation in Q&A posts in four 'Ask' subreddits, identifying eight categories of posts: Explanation (with disagreement, with agreement, and with neutral presentation); Socializing (with negative or positive intent); Providing References; Information Seeking; and Community Rules and Norms.…”
Section: Learning Goalsmentioning
confidence: 99%
“…Engagement on SO is an example of 'learning in the wild' [20], i.e., an informal and non-formal selforganizing learning environment where crowds of participants ask, answer, comment, correct, argue, and make the effort to present information in informed and accessible ways, while also monitoring content, value, and appropriate behavior. While based on crowd participation, these environments are also communities: epistemic communities, based on a common orientation to a particular knowledge domain [44]; discourse communities, understanding and employing particular language and genre of communication [45]; and communities of practice, with common goals and orientations [34].…”
Section: Introductionmentioning
confidence: 99%
“…Content or thematic analysis are suitable for analysing Reddit posts. For example, an assessment of comments posted to four question-based subreddits in 2015/2016 found that explanations with disagreements accounted for about half of the r/ask_Politics comments, whereas neutral explanations accounted for about half of the comments in the remaining subreddits (askAcademia, askScience, askHistorians) (Kumar, Gruzd, Haythornthwaite, Gilbert, Esteve del Valle & Paulin, 2018). Less common activities included socialising, information seeking and providing resources.…”
Section: Redditmentioning
confidence: 99%